Aplicação da semiótica na investigação do posicionamento percebido: um estudo no setor da indústria de artigos esportivos - Potrich, Susana Zanetti (2023)
The present study has as its objective to analyze the Draggon Sports company positioning facing the main competitors in the sportswear segment. In the positioning process, the brands need to function as a “compressed file” in the consumer’s mind and, when opened, presents the offer proposal through association unfolding. Brands represent the consumers’ perceptions and feelings related to a product an its performance. In order to investigate the realized positioning, it was used qualitative and exploratory approach from semiotics. The study investigated four brands positioning in the sportswear segment with 16 people chosen by convenience. Three metaphorical icon groups (sneakers brands, automobiles and animals) were established as metaphorical signs to which the people from the sample relate themselves and associates with four sportwear brands investigated, establishing determinant characteristics to the positioning. As main result, the study afforded the realized positioning to the Draggon Sports brand in relation to the competitors, demonstrating this brand is noted as the market leader in the region, through the customers’ views, and the company is specialized in its market segment. Thus, it stands out that semiotics science is relevant to the access of researchers to elements concealed by rationality among consumers, so as it is also necessary the quantitative studies development, observing the methodology for analysis proposed by Peirce.